Conflicting Futures, Entangled Pasts: Nigerian Missionaries in a Post-secular Europe? - Knibbe, Kim Esther (PentecoStudies, 2019)
Scholars studying Pentecostalism unite in networks such as the GloPent network (represented by this journal) on the basis of the fact that across the globe, we observe the emergence, growth and evolution of organization and networks that are similar, yet also quite strongly rooted in the local context. The emergence of missionary activities from Nigeria and other countries of what is often called the “Global South” is a new phase in the history of Pentecostalism that has now been ongoing for a while. It calls into question the relationship between local contexts and global religious phenomena in new ways: how can we understand these movements as shaped both by “local contexts” (of, in this case Nigeria), as well as part of a global network of Pentecostal movements, in the way they relate to the “local context” of a country that is a former colonial power (and current resource extractor and job provider, via Shell), namely the Netherlands? In this article I want to take a step back and attend to the question: what do we study when we study Nigerian Pentecostal missionaries in Europe? Furthermore, through attending the dimension of time I will explore how this phase in the history of Global Pentecostalism may give new insights into the new complexities of Europe.